Consensus guidelines for implementation of quality processes to prevent invasive fungal disease and enhanced surveillance measures during hospital building works, 2014. Issue 12 (December 2014) - Chang, C. C.; Ananda‐Rajah, M.; Belcastro, A.; McMullan, B.; Reid, A.; Dempsey, K.; Athan, E.; Cheng, A. C.; Slavin, M. A.
Abstract Healthcare‐associated fungal outbreaks impose a substantial economic burden on the health system and typically result in high patient morbidity and mortality, particularly in the immunocompromised host. As the population at risk of invasive fungal infection continues to grow due to the increased burden of cancer and related factors, the need for hospitals to employ preventative measures has become increasingly important. These guidelines outline the standard quality processes hospitals need to accommodate into everyday practice and at times of healthcare‐associated outbreak, including the role of antifungal stewardship programmes and best practice environmental sampling. Specific recommendations are also provided to help guide the planning and implementation of quality processes and enhanced surveillance before, during and after high‐risk activities, such as hospital building works. Areas in which information is still lacking and further research is required are also highlighted.